Aplikasi Teknologi Mesin Tetas Otomatis Pada Peternak Ayam Kampung Desa Opaasi Kecamatan Ranomeeto Barat Kabupaten Konawe Selatan - Has, Hamdan; Rusdin, Muh.; Yaddi, Yamin; Badarudin, Rusli; Napirah, Astriana (Indonesian Journal of Community Services, 2022)
Kampong chicken is one of the most common types of poultry bred by people throughout Indonesia. Kampong chickens have several limitations such as relatively slow growth and low egg production. One solution to overcome this is by utilizing hatching using an incubator. The incubator can eliminate the brooding period in the brood so that the hen can be more productive and able to produce more eggs. This Bina Desa activity was carried out in Opaasi Village, South Konawe Regency with kampong chicken farmers as target partners. This activity involves a team of lecturers from the UHO Faculty of Animal Science and is carried out in several stages, namely: socialization, technical guidance on making hatching machines, hatching assistance, and evaluation of activities. The result of this activity is that it can provide additional knowledge and skills to native chicken farmers about the manufacture of hatching machines and their technical use of them.